1981
DOI: 10.1038/clpt.1981.102
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between amrinone plasma concentration and cardiac index

Abstract: Amrinone was given to 14 patients with congestive heart failure as an intravenous bolus (1 mg/sec) at doses ranging from 0.5 to 3.5 mg/kg. Simultaneous determinations of cardiac index were made by thermodilution and of amrinone plasma concentration by high-performance liquid chromatography. A relationship between improvement in cardiac index and increasing plasma concentrations of amrinone was demonstrated for 13 of the 14 patients. The percentage increase in cardiac index correlated with amrinone plasma conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Similar results were obtained by Wilson et al [77] and Rocci et al [78]. An even longer half-life (8.3 hours) after oral amrinone (150-300 mg) was found in patients with severe, chronic congestive HF (NYHA class III and IV; cardiac index, < 2.5 1/min/m 2) [79]. An even longer half-life (8.3 hours) after oral amrinone (150-300 mg) was found in patients with severe, chronic congestive HF (NYHA class III and IV; cardiac index, < 2.5 1/min/m 2) [79].…”
Section: Amrinonesupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were obtained by Wilson et al [77] and Rocci et al [78]. An even longer half-life (8.3 hours) after oral amrinone (150-300 mg) was found in patients with severe, chronic congestive HF (NYHA class III and IV; cardiac index, < 2.5 1/min/m 2) [79]. An even longer half-life (8.3 hours) after oral amrinone (150-300 mg) was found in patients with severe, chronic congestive HF (NYHA class III and IV; cardiac index, < 2.5 1/min/m 2) [79].…”
Section: Amrinonesupporting
confidence: 87%
“…No significant differences in the kinetic parameters were noted between single and repeated doses (steady state) [78]. The kinetic modifications observed in these patients are probably related to the decreased blood flow to the kidney and the liver that is associated with congestive HF [79]. The kinetic modifications observed in these patients are probably related to the decreased blood flow to the kidney and the liver that is associated with congestive HF [79].…”
Section: Amrinonementioning
confidence: 99%
“…The range of epinephrine had been demonstrated in pilot studies to cause an increase of %SS comparable with that observed during dobutamine infusion. The blood concentrations for each inotropic agent examined include the clinical dose range (dobutamine, 0.1-0.2 µg/mL; amrinone 2-7 µg/mL) (14, 15). Each inotropic drug was infused for 3 to 5 min in incremental doses administered 8 to 10 min apart each.…”
Section: Methodsmentioning
confidence: 99%
“…Edelson et al [139] measured plasma concentrations of amrinone in adult patients with congestive heart failure following an intravenous bolus injection of 0.5 to 3.5 mg/kg of body weight, with simultaneous measurement of cardiac index. A direct linear correlation between the percentage increase in cardiac index and amrinone plasma concentration was demonstrated over a range of 0.5 to 7 mg/L, with a 50% increase in cardiac index corresponding to a plasma concentration of 3.7 mglL.…”
Section: Amrinonementioning
confidence: 99%